A defective type 1 response to rhinovirus in atopic asthma. Issue 4 (1st April 2002) - Papadopoulos, N G; Stanciu, L A; Papi, A; Holgate, S T; Johnston, S L
Abstract : Background: Rhinoviruses (RVs) are the most frequent precipitants of the common cold and asthma exacerbations, but little is known about the immune response to these viruses and its potential implications in the pathogenesis of asthma. Methods: Peripheral blood mononuclear cells (PBMC) from patients with atopic asthma and normal subjects were exposed to live or inactivated RV preparations. Levels of interferon (IFN)γ and interleukins IL-12, IL-10, IL-4, IL-5 and IL-13 were evaluated in the culture supernatants with specific immunoassays. Results: Exposure of PBMC to RVs induced the production of IFNγ, IL-12, IL-10, and IL-13. Cells from asthmatic subjects produced significantly lower levels of IFNγ and IL-12 and higher levels of IL-10 than normal subjects. IL-4 was induced only in the asthmatic group, while the IFNγ/IL-4 ratio was more than three times lower in the asthmatic group. Conclusions: This evidence suggests that the immune response to RVs is not uniquely of a type 1 phenotype, as previously suggested. The type 1 response is defective in atopic asthmatic individuals, with a shift towards a type 2 phenotype in a way similar, but not identical, to their aberrant response to allergens. A defective type 1 immune response to RVs may be implicated in the pathogenesis of virus induced exacerbations of asthma.